Multiple Rieske Iron Sulfur Proteins of Photosynthesis in the Cyanobacterium Synechocystis SP PCC 6803 - Ranade, Saurabh J. (My University, 2012)
The cytochrome bf complex is essential for both photosynthetic and respiratory electron transport in cyanobacteria. A Rieske iron-sulfur protein (ISP) is an essential subunit of this complex. The cyanobacterium, Synechocystis sp. PCC 6803 carries three genes, petC1, petC2, petC3, for different forms of Rieske ISPs. PetC1 is the major ISP. The functions of the PetC2 and PetC3 ISPs are not well understood. My goal was to investigate the roles of these Rieske proteins in electron transfer and redox signaling mediated by the cytochrome bf complex. Wild type Synechocystis and a mutant strain (PetC1) that lacks the PetC1 ISP and thus uses the PetC2 ISP in its cytochrome bf complex were used for these studies. These strains were grown photosynthetically followed by shifts to dark aerobic and anaerobic conditions to test the postulated role of the PetC2 Rieske ISP in dark metabolism. Expression of the three Rieske ISP genes and control genes (psaC, for a photosystem I subunit; zwf, for glucose-6-phosphate dehydrogenase; and rpnB, for an RNAse P subunit) was investigated by reversetranscriptase quantitative polymerase chain reactions (RT-qPCR). The relative abundance of photosystem and cytochrome bf proteins in the wild type and PetC1 mutant strain was investigated by liquid chromatography, tandem mass spectrometry (LC-MS/MS). Electron transfer reactions were investigated by light-induced, kinetics spectroscopy to gain information about relative quantities of electron transfer protein complexes and components in the wild type and PetC1 strains and to compare the catalytic efficiencies of the PetC1 and PetC2 Rieske ISPs. RT-qPCR data from the wild type showed elevated expression of petC2 relative to petC1 during dark anaerobiosis and greatly increased petC2 expression, as might be expected, in the PetC1 mutant. Gene expression and other data suggests that PetC3 has a function independent of the cytochrome bf complex. Kinetics spectroscopy data suggest that the PetC1 mutant has a highly unusual cytochrome bf complex consisting primarily of the PetC2 Rieske ISP and cytochrome b6 proteins. Surprisingly, the latter is kinetically coupled despite a very low content of the normally essential cytochrome f protein. The kinetics data further indicate that the PetC1 and PetC2 Rieske iron-sulfur proteins have similar catalytic efficiencies. Questions remain as to the specific roles of the PetC2 and PetC3 Rieske proteins. Overall, the research contributes to understanding electron transfer pathways and mechanisms by which cyanobacteria adapt to changing environments. This knowledge will be important for engineering cyanobacterial electron transfer pathways for biofuels applications.
A Thesis Submitted In Partial Fulfillment of the Requirements For the Degree of Master of Science-Biology
Keywords: Photosynthesis; Cyanobacteria; Electron transfer; Iron-sulfur proteins